An empirical test of measures of housing degrowth: Learning from the limited experience of England and Wales, 1981–2011. (May 2023) - Tunstall, Rebecca
This article builds on the concept of 'degrowth' to create an experimental, measurable definition of 'housing degrowth', which can be applied to the 99% of households in mainstream housing. Like 'degrowth', housing degrowth runs against housing policy which has assumed that more housing is good. The article explores whether measurement of housing degrowth is possible with existing data, and whether any housing degrowth has occurred in the existing pro-growth housing system in England and Wales. Building on Kallis et al., 'housing degrowth' is defined as a reduction of the total resources going into housing production and use, without an increase in inequality or a loss of wellbeing. First, using the total number of rooms as a proxy, over 1981–2011, England and Wales experienced significant increases in embodied CO2 (from housing construction, maintenance and disposal). Only a handful of areas experienced reductions, even in resources per person, and in these, inequality increased, and some had very little space per person for the worst-off, likely to harm wellbeing. Second, estimated data on direct CO2 production by homes in use 2008–18 showed a reduction, which was equitable between income and tenure groups. However, the poorest were hit hardest by rising energy costs, likely to have depressed wellbeing, again failing the degrowth definition. In conclusion, assessing broad trends in housing degrowth is possible, even with imperfect data. Future intentional degrowth appears possible, but will need more political justification, changes to incentives and regulation, and a focus on those worst-off.